DEFENSE MECHANISM OF TYRION LANNISTER IN GAME OF THRONES FILM SERIES - Bahtiar, Bahtiar; Kuncara, Singgih Daru; Lubis, Indah Sari (Fakultas Ilmu Budaya Universitas Mulawarman, 2022)
The objective of this research is to describe the categories of defense mechanism used by Tyrion Lannister. Sigmund Freud’s theory of defense mechanism and personality theory is used by the researcher to answer the research question. This research uses qualitative descriptive method. The data of this research are scenes and dialogues of Tyron Banister including dialogues and scenes from other characters that contain the defense mechanism used by Tyron. The data analysis was conducted through observation, collecting, identifying, and classifying data to find the necessary data for the research. The findings of the research are as follows: in the Third and Fourth season of Game of Thrones film series created by David Benioff and D.B Weiss, all twelve defense mechanisms are found. Those are; Ten data of denial, thirty data of rationalization, two data of projection, four data of sublimation, eight data of reaction formation, two data of displacement, three data of regression, three data of undoing, six data of identification, five data of compensation, eighteen data of humor, and three data of repression. The cases of defense mechanisms used by Tyron gained through character and characterization. Character and characterization are necessary to understand certain situations in the story, it helps the researcher to determine the cause of the events and how the character reacts to it via indirect characterization or actions. Furthermore, character and characterization define what kind of defense mechanisms that are used by the character to work through his problems such as being despised, mocked, and humiliated.